Policy Options for Liberalizing Philippine Maritime Cabotage Restrictions - World Bank Group (World Bank, Washington, DC, 2016)
The purpose of this policy note is to present reform options on cabotage liberalization. The goal of cabotage liberalization is to help i) foster more competition in the domestic shipping industry, ii) reduce shipping cost, and iii) improve efficiency, maritime services, and safety standards. These, together with complementary reforms in domestic shipping and ports, can help enhance consumer and producer welfare through lower consumer prices, higher household real income, timely delivery of goods, and ultimately, job creation and poverty reduction through greater market access. This policy note on cabotage is organized as follows. Part one provides an overview of the domestic shipping industry and discusses the key issues that it faces. Part two discusses the underlying reasons for the industry’s inefficiency. Part three discusses the concept of cabotage, the cost and benefit of cabotage liberalization, and the cabotage regimes of the Philippines and of selected countries. Part four closes with a discussion of reform options.